Health-Promoting Lifestyle in Colorectal Cancer Survivors: A Qualitative Study on the Experiences and Perspectives of Colorectal Cancer Survivors and Healthcare Providers - Elahe Ramezanzade Tabriz; Monir Ramezani; Abbas Heydari; Seyed Amir Aledavood (Elsevier, 2021)
Objective: Understanding the experiences of survivors and healthcare providers about health-promoting lifestyle (HPL) in colorectal cancer (CRC) survivors is important in planning for coping with the disease, managing treatment side effects, increasing survival, and improving quality of life (QOL). This study was conducted to explore the experiences and perspectives of CRC survivors and healthcare providers about HPL in CRC survivors. Methods: This descriptive qualitative study was performed in 2020 at Omid and Imam Reza Hospitals in Mashhad, Iran. Participants were CRC survivors (n = 12) and healthcare providers (n = 33) who were selected by purposive sampling. Data were collected using in-depth semi-structured interview by face to face and then analyzed by Zhang and Wildemuth content analysis method. MaxQDA software was used to organize the data. Results: Following the treatment of cancer, CRC survivors seek to make changes in lifestyle and they choose a HPL that maintains or improves their health. HPL in CRC survivors includes nutrition, activity and rest, health responsibility, interpersonal relations, spiritual growth, and psychological management. The results showed that HPL can lead to motivation, the ability to self-care and improve daily performance, reduce treatment complications, and increase the QOL. Conclusions: CRC survivors can help change their lifestyle patterns with healthy eating, treatment adherence, regular physical activity, and good sleep habits. Furthermore, effective personal and social relationships, spiritual growth, and management of psychological disorders develop health-promoting behaviors in them. CRC survivors also face challenges and limitations in their life after treatment; identifying the components of a HPL in CRC survivors can lead to desirable care, treatment, education, and counseling services.